THE TOUR OF THE BREED AND BREEDING OF KAZILARNING MEAT PRODUCTIVITY (American Journal of Interdisciplinary Research and Development, 2025)
The article presents the fact that the meat productivity of sheep can change depending not only on the conditions of their feeding and maintenance but also on their breed and breed. It was found that rams from the III group of the breed ¾ edilboy x ¼ jaidari, had higher meat productivity, at the age of 12 and 18 months of development, than crossbred lambs from the I group of purebred jaidari and in the II group of pure jaidari and crossbred ½ edilboy x ½ jaidari.